Closed residential spaces: differentiated and unequal access to land in the city of Matola – Mozambique - Ribeiro, Ester Tomás Natal (GEOUSP Espaço e Tempo (Online), 2022)
The main objective of this article is to characterize the closed residential spaces (CRS) in the Matola City, considering the differentiated and increasingly unequal access to land for its implementation and occupation. With the intensification of urban processes in Matola City , there is notable an increase in demand for land and implementation of CRS, which constitute a new way of living in Mozambique in general and in particular in Matola City, whose production is purely commercial and profitable. This analysis becomes relevant, first, because the CRS are urban elements restricted to minorities due to the high monetary values ​​for their acquisition, making them spaces of self-segregation. Second, because the land is owned by the State of Mozambique, the sale of which is prohibited, even though its possession is considered a condition of production and private property is valued in the capitalist mode of production.